Enhancement of thermoelectric performance in a non-toxic CuInTe2/SnTe coated grain nanocomposite. Issue 26 (22nd June 2021) - Hwang, Junphil; Lee, Minju; Yu, Byung-Kyu; Han, Mi-Kyung; Kim, Woochul; Kim, Jungwon; Al Rahal Al Orabi, Rabih; Wang, Hongchao; Acharya, Somnath; Kim, Jiyong; Jin, Yingshi; Park, Hwanjoo; et al.
Abstract : A new design strategy to synthesize a toxic-free coated grain nanocomposite. Synergetic enhancement of thermoelectric performance by energy filtering and coherent phonon scattering. Abstract : A thermoelectric coated grain nanocomposite CuInTe2 /SnTe with eco-friendly elements was synthesized. The nanocomposite contains a coating layer of CuInTe2 and SnO2 at the grain boundaries of the SnTe matrix. The coating layer was synthesized using the cation exchange process considering the hard soft acid base (HSAB) concept, the solubility product, and crystal structure. The CuInTe2 coating layer blocks the low energy carriers of the composite resulting in 40% enhancement of the Seebeck coefficient due to energy filtering. The coherent phonon scattering by the coating layer of CuInTe2 effectively reduces the lattice thermal conductivity to almost the minimum theoretical limit. The thermoelectric figure of merit ( zT ) for the CuInTe2 /SnTe nanocomposite was as high as 1.68 at 823 K, which is significantly higher than that of bulk SnTe in the mid-temperature range. The average zT from 373 K to 823 K for the nanocomposite was 0.76, which is promising for utilization in industrial application.